Perencanaan Pemasaran Tahu Tuna pada Usaha Mikro Nabilla Makmur di Pacitan, Jawa Timur - PUTRI, NI LUH MADE RATNA HAPSARI; DARMAWAN, DWI PUTRA; WIJAYANTI, PUTU UDAYANI (Jurnal Agribisnis dan Agrowisata (Journal of Agribusiness and Agritourism); Vol.7, No.1, Januari 2018, 2018)
Marketing Plan of Tuna Tofu at Micro Enterprise Nabilla Makmur in Pacitan, Eats Java This study aimed to know the marketing plan of tuna tofu micro business of Nabilla Makmur in 2017 as a new pioneered business unit and having a bright sales prospect.. The data analysis used Smart Business Plan 8.0 program consisting of marketing plan variables. The company did not implement the target in sales, but within one month the company was able to produce up to 1,500 packs per month. Based on the results of internal and external factors analysis by maximizing the strength and exploiting the existing opportunities and minimizing the weaknesses and threats from outside by improving the quality of tuna tofu products and services to consumers, looking for new potential supplier areas, promotion through internet and mass media and additional personnel as company sales, and cooperation with gift shop around Pacitan.The strategy adopted by the company was a marketing mix strategy which consists of product strategy using packaging system using vacuum plastic, pricing strategy based on competitor price, and cost of principle sale price in determining selling price of tuna tofu, company distribution strategy through local sales in Pacitan city and sales in out of Pacitan city covering some big cities in Indonesia, company promotion strategy with good company name and through social media.